2008
DOI: 10.1177/1077801208320248
|View full text |Cite
|
Sign up to set email alerts
|

When Will Adolescents Tell Someone About Dating Violence Victimization?

Abstract: This study examined factors that influence help-seeking among a diverse sample of adolescents who experienced dating violence. A sample of 57 high school students in an urban community reported on the prevalence and characteristics of dating violence in their relationships. Someone observing a dating violence incident and a survivor's attaching an emotional meaning to the event significantly influenced adolescents to talk to someone. When dating violence occurred in isolation, survivors were more likely to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
0
15

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(137 citation statements)
references
References 36 publications
12
110
0
15
Order By: Relevance
“…12,38 When they do tell someone, they usually turn to their peers, not parents, teachers, or school counselors. 39 Thus, school counselors must become more active regarding anticipatory guidance of ADV to help prevent and to encourage reporting of ADV to trusted school authorities and health care providers. A number of studies have reported specific information on how to help reduce ADV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,38 When they do tell someone, they usually turn to their peers, not parents, teachers, or school counselors. 39 Thus, school counselors must become more active regarding anticipatory guidance of ADV to help prevent and to encourage reporting of ADV to trusted school authorities and health care providers. A number of studies have reported specific information on how to help reduce ADV.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported specific information on how to help reduce ADV. 20,34,[37][38][39][40] Finally, school counselors and pediatricians need to reach out to one another to form partnerships between counselors and providers to help augment their training on anticipatory guidance strategies and skill building in dealing with ADV.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, only recently this topic has aroused the interest of the scientific community. Youth and adolescents of both sexes can be victims of dating violence, but often have difficulty recognizing it as such and rarely seek help 35 . A study conducted in Recife, Brazil, found that 19.9% of adolescents had loving relationships in the last year have perpetrated an act of physical violence and 82.8% of psychological violence 36 .…”
Section: Dimension 1 Dimensionmentioning
confidence: 99%
“…The results concerning female adolescents are clearer and more coherent: They suffer more IPV than male adolescents do, and this violence is likely to be more severe (Molidor & Tolman, 1998;Poitras & Lavoie, 1995); when exposed to IPV, they react with more emotional distress and present more mental health problems than males. Adolescent boys suffer less partner violence and are likely to experience this violence as less threatening than that suffered by girls (Black, Tolman, Callahan, Saunders, & Weisz, 2008;Fineran, 2002). However, this result may be affected by underreporting of subjective reactions to IPV.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%